Influence of External Pressure, Financial Stability, and Financial Target on Fraud Financial Reporting - Bambang Subiyanto; Tiara Pradani; Dinda Tri Novianty Divian (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to obtain empirical evidence of how the influence of external pressure, financial stability, and financial targets on fraudulent financial reporting in manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2016-2020. The population in this study is manufacturing companies in the consumer goods industry listed on the Indonesia Stock Exchange through the website www.IDX.co.id during the period 2016-2020. The sample in this study were 14 manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange from 2016 to 2020, which were selected using the purposive sampling method. The type of data used in this research is secondary data. Techniques and data collection tools in this study used the method of documentation and literature study. While the data analysis method used is multiple linear regression analysis. The results obtained in this study indicate that external pressure and financial targets have a significant negative effect on financial statement fraud. Meanwhile, financial stability has no significant effect on fraudulent financial statements.